Hippopotamus and livestock grazing near water points: consequences for vegetation cover, plant species richness and composition in African savannas - Kanga, Erustus M.; Ogutu, Joseph O.; Piepho, Hans-Peter; Olff, Han (Frontiers in Ecology and Evolution, 2023)
Large herbivore grazing can fundamentally alter vegetation composition and structure, especially around rivers. However, distinctions in how riparian savanna vegetation responds to livestock and hippo grazing are still poorly understood. We therefore investigated differences in vegetation structure, species richness and composition along distance from rivers between a protected reserve grazed predominantly by hippos and adjoining pastoral ranches grazed mostly by livestock in wet and dry seasons. In both landscapes, riverine areas were more intensely and homogeneously grazed in the pastoral ranches and in the dry season. Moreover, grazing intensity decreased away from rivers in the reserve in both seasons, but only in the wet season in the pastoral ranches. The mean plant species richness was similar in both landscapes and decreased away from rivers, but varied with grazing intensity due to differences in forb and shrub species. Plant species composition differed between the reserve and the pastoral ranches. Furthermore, species similarity indices declined with increasing distance from water. Hence, impacts of livestock and hippo grazing intensity on vegetation structure and spatial heterogeneity interact, and vary with landscape and season. Livestock grazing impact on vegetation species composition, structure and spatial heterogeneity is more persistent and declines less rapidly away from water.